How to manage unresponsiveness to misoprostol in failed second trimester pregnancy termination - Saipin Pongsatha (2018)
Aim: To present the experience of management of second trimester pregnancy termination by misoprostol after failure to abort within 48 h of its use. Material and Methods: A retrospective, cohort descriptive study was carried out in the Department of Obstetrics and Gynecology, Faculty of Medicine, Chiang Mai University Thailand between 1998 and 2010. All women at 14-28 weeks of gestation who failed to abort using misoprostol within 48 h were included. Management of failed pregnancy termination among these women is described here. Results: Of a total of 680 women undergoing termination of pregnancy, 68 (10%) failed to abort. Mean maternal age was 28.71 years and mean gestational age was 19.91 weeks. Further management after failure included additional administration of misoprostol only (19.1%), modified condom balloon technique only (17.7%), modified condom balloon technique plus other methods (16.1%), while 47.1% needed only oxytocin as necessary. The mean interval between initiation of termination and delivery was 96.97 h. Conclusion: Failure of pregnancy termination using misoprostol can be successfully managed by introducing additional misoprostol, modified condom balloon technique and oxytocin infusion. These methods should be considered before proceeding to hysterotomy. © 2012 The Authors.